PENGARUH FINANCIAL LEVERAGE TERHADAP PROFITABILITAS (Studi pada Perusahaan Industri Kimia yang Listing di BEI Periode 2009-2013) - Dini Kurniawati (Fakultas Ilmu Administrasi Universitas Brawijaya, 2015)
The main objective of study is to examine influence of degree of financial leverage (DFL), debt ratio (DR), total debt to equity ratio (DER) and time interest earned ratio (TIER) on return on equity (ROE) simultaneously and partially and examine independent variable that dominant influence. This type of study is explanatory. The sampling method is purposive sampling. Thus, the sample in this study amounted to 9 Chemical Industry Companies listed on IDX in period 2009-2013. The method of data analysis is multiple linear regression. Based on f test result was obtained F value is 4,209 and significant value is 0,006 with F table is 2,61 (0,05). That means simultaneously effects of DFL, DR, DER and TIER are significant on ROE. Adjusted R2 value is 22,60%. So, ROE can be explained by DFL, DR, DER and TIER amounted to 22,60%. The obtained t value of DFL is –0,525, DR is 2,590, DER is –2,610 and TIER is 2,639 with t table is 2,021 (0,05). Significant value of DFL is 0,602, DR is 0,013, DER is 0,013 and TIER is 0,012. That means, in partial, the effect of DFL is not significant on ROE, but DR, DER and TIER partially and significantly influence ROE. Standardized coefficients beta of DR is 1,090 and it has the highest coefficient. It means independent variable that dominant influence ROE is DR. Keywords: Degree of Financial Leverage (DFL), Debt Ratio (DR), Total Debt to Equity Ratio (DER), Time Interest Earned Ratio (TIER), Return On Equity (ROE)ABSTRAKPenelitian dilakukan untuk menjelaskan seberapa besar degree of financial leverage (DFL), debt ratio (DR), total debt to equity ratio (DER) dan time interest earned ratio (TIER) secara serentak maupun individu berpengaruh terhadap return on equity (ROE) dan mana yang berpengaruh dominan. Jenis penelitian yaitu explanatory research. Purposive sampling dipilih sebagai teknik untuk mengambil sampel. Sampel berjumlah 9 Perusahaan Industri Kimia yang listing di BEI periode 2009-2013. Data dianalisis dengan regresi linier berganda. Hasil uji F menjelaskan F hitung sebesar 4,209 dan nilai signifikan sebesar 0,006 dengan F tabel sebesar 2,61 (0,05). Hasil menunjukkan DFL, DR, DER dan TIER secara serentak signifikan berpengaruh terhadap ROE. Nilai adjusted R2 sebesar 22,60% maka ROE dijelaskan oleh DFL, DR, DER dan TIER sebesar 22,60%. Hasil uji t menjelaskan t hitung DFL sebesar –0,525, DR sebesar 2,590, DER sebesar –2,610 dan TIER sebesar 2,639 dengan t tabel sebesar 2,021 (0,05). Nilai signifikan DFL sebesar 0,602, DR sebesar 0,013, DER sebesar 0,013 dan TIER sebesar 0,012. Hasil menunjukkan DFL secara individu tidak signifikan berpengaruh terhadap ROE. DR, DER dan TIER secara individu signifikan berpengaruh terhadap ROE. Standardized coefficients beta DR sebesar 1,090 dan tertinggi diantara independent variable yang lain maka DR berpengaruh dominan terhadap ROE.Kata kunci: Degree of Financial Leverage (DFL), Debt Ratio (DR), Total Debt to Equity Ratio (DER), Time Interest Earned Ratio (TIER), Return On Equity (ROE)